Életformák 2
Program host Dr. Ilona Nagy, continuation of talking with Erzsébet Eisner, Győző R. Mátrai, changes in lives, questions from audience, success, happiness, image, taste, feeling, body, goal, plans for the year, future, realistic desires, ability to change András Surányi